SeDiCI (Intellectual Creation Diffusion Service) - De Giusti, Marisa Raquel (2007)
The Intellectual Creation Diffusion Service (SeDiCi) of the UNLP was created with the main objective of communicating to the society all the knowledge acquired in different academic fields of our university. This is how we can return all the efforts that were destined to our public institution.